Films that Work Industrial Film and the Productivity of Media - Vonderau, Patrick; Hediger, Vinzenz (Film Culture in Transition, 2009)
The history of industrial films - an orphan genre of twentieth-century cinema composed of government-produced and industrially sponsored movies that sought to achieve the goals of their sponsors, rather than the creative artists involved - seems to have left no trace in filmic cultural discourse. At its height the industrial film industry employed thousands, produced several trade journals and festival circuits, engaged with giants of twentieth-century industry like Shell and AT & T, and featured the talents of iconic actors and directors such as Buster Keaton, John Grierson and Alain Resnais. This is the first full-length book, anthology, and annotated bibliography to analyse the industrial film and its remarkable history. Exploring the potential of the industrial film to uncover renewed and unexplored areas of media studies, this remarkable volume brings together renowned scholars such as Rick Prelinger and Thomas Elsaesser in a discussion of the radical potential and new possibilities in considering the history of this unexplored corporate medium.